BSRs Elevated by Fluid Upwelling on the Upper Amazon Fan : Bottom-up Controls on Gas Hydrate Stability - Praeg, Daniel; Silva, Cleverson; dos Reis, Antonio; Ketzer, J. M.; Unnithan, Vikram; Perovano, R. J.; Cruz, Alberto; Gorini, Christian (HAL CCSD, 2017)
International audience The stability of natural gas hydrate accumulations on continental margins has mainly been considered in terms of changes in seawater pressures and temperatures driven from above by climate. We present evidence from the Amazon deep-sea fan for stability zone changes driven from below by fluid upwelling. A grid of 2D and 3D multichannel seismic data show the upper Amazon fan in water depths of 12002000 m to contain a discontinuous bottom simulating seismic reflection (BSR) that forms 'patches' 1050 km wide and up to 140 km long, over a total area of at least 5000 km. The elongate BSR patches coincide with anticlinal thrust-folds that record ongoing gravitational collapse of the fan above décollements at depths of up to 10 km. The BSR lies within 100300 m of seafloor, in places rising beneath features that seafloor imagery show to be pockmarks and mud volcanoes, some venting gas to the water column. The BSR patches are up to 500 m shallower than predicted for methane hydrate based on geothermal gradients as low as 17˚C/km measured within the upper fan, and inversion of the BSR to obtain temperatures at the phase boundary indicates gradients 25 times background levels. We interpret the strongly elevated BSR patches to record upwelling of warm gas-rich fluids through thrust-fault zones 10 km wide. We infer this process to favour gas hydrate occurrences that are concentrated in proportion to flux and locally pierced by vents, and that will be sensitive to temporal variations in the upward flux of heat and gas. Thus episodes of increased flux, e.g. during thrusting, could dissociate gas hydrates to trigger slope failures and/or enhanced gas venting to the ocean. Structurally-driven fluid flow episodes could account for evidence of recurrent large-scale failures from the compressive belt on the upper fan during its Neogene collapse, and provide a long-term alternative to sea level triggering. The proposed mechanism of upward flux links the distribution and stability of gas hydrate occurrences ...